Government vs opposition voting in the Finnish parliament Eduskunta since World War II - Antti Pajala (European Journal of Government and Economics, 2013)
In a parliamentary system it is by definition justified to assume the government parties voting almost always in a unitary manner in plenary votes. In a multiparty system it is, however, hard to predict how the opposition groups vote. Few studies analysing government-opposition voting in the Finnish parliament Eduskunta were published during the 1960s and 1970s. This study provides similar analyses regarding the parliamentary years of 1991-2012. Combined the studies provide an insight into the government-opposition relations since World War II. The results show that before the 1990s the government-opposition division in plenary votes appeared rather clear and the political party groups’ positions followed the traditional left-right dimension. Since the 1990s, the government-opposition division has become greater. The governing coalition acts almost as a bloc while the opposition groups are divided into moderate and hard opposition. The opposition groups, however, appear in a more or less random order. Consequently, since the 1990s the left-right dimension has disappeared with respect to plenary voting.